2019
DOI: 10.1111/jep.13229
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty of the decision‐making process in emergency departments for end‐of‐life patients

Abstract: Background In emergency departments, for some patients, death is preceded by a decision of withholding or withdrawing life‐sustaining treatments. This concerns mainly patients over 80, with many comorbidities. The decision‐making process of these decisions in emergency departments has not been extensively studied, especially for noncommunicating patients. Aim The purpose of this study is to describe the decision‐making process of withholding and withdrawing life‐sustaining treatments in emergency departments f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
2
14
1
1
Order By: Relevance
“…Because of the lack of ADs, family members need to express patients' wishes concerning their end-of-life preferences. [31] Kwok et al [32] found that most family surrogates had poor knowledge of lifesustaining treatments, and most of them depended on their views but not the patients' wishes to make the fi nal DNR directives. By tradition, the eldest son or daughter is obliged by fi lial piety to do everything to prolong the elderly patient's life; the opinions of family members and health-care professionals take precedence over personal opinions or preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of ADs, family members need to express patients' wishes concerning their end-of-life preferences. [31] Kwok et al [32] found that most family surrogates had poor knowledge of lifesustaining treatments, and most of them depended on their views but not the patients' wishes to make the fi nal DNR directives. By tradition, the eldest son or daughter is obliged by fi lial piety to do everything to prolong the elderly patient's life; the opinions of family members and health-care professionals take precedence over personal opinions or preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most patients didn't have advance directives before admission in the ED. 15 It could help to avoid sending them to the ED. It has been found that the main perceived barriers of GP-patient communication in palliative care are the lack of availability of GPs and also GPs' ambivalence to discuss 'bad prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…End‐of‐life decisions present another area where the meaningful application of person‐centred approaches and SDM seems at once eminently important and particularly difficult to implement. Marion Douplat et al conducted a prospective multicentre study in three emergency departments of university hospitals in France, to describe the management of the decision‐making process of withholding and withdrawing life‐sustaining treatments. The results made it clear that there is still very little anticipation in end‐of‐life decisions, and the authors conclude that “discussion with patients concerning their end‐of‐life wishes as well as the writing of advance directives, especially for patients with chronic diseases, must be encouraged early.”…”
Section: Shared Decision Makingmentioning
confidence: 99%
“…It includes papers on the nature of reasoning and evidence, the on‐going problems of how to “integrate” different forms of scientific knowledge with each other, and with broader, humanistic understandings of reasoning and judgement, patient and community perspectives . Discussions of the epistemological contribution of patient perspectives to the nature of care, and the crucial and still under‐developed role of phenomenology in medical epistemology, are followed by a broad range of papers focussing on SDM, analysing its proper meaning, its role in policy, methods for realizing it and its limitations in real‐world contexts …”
Section: Introductionmentioning
confidence: 99%